(untitled) (Research, Society and Development, 2021)
The Internet of Things (IoT) network in the health area offers many facilities or conveniences, as it allows communication between machines, such as monitoring the development of chronic diseases, disseminating disease control, monitoring the fall of the elderly. However, this communication can bring some associated risks, such as breach of privacy and security, loss of data integrity. Thus, this study identified the components of the network that interfere with the occurrence of risk and their respective hierarchy within the IoT system used in the health area. There were 8 (eight) factors identified in the literature and were validated by 2 (two) academic experts with knowledge on the subject. The use of the Analytic Hierarchy Process (AHP) method allowed to identify the most critical componentes related to the study proposed here.